Quantitative anal sphincter EMG in multisystem atrophy and 100 controls. Issue 5 (1st November 2001) - Gilad, R; Giladi, N; Korczyn, A D; Gurevich, T; Sadeh, M
Abstract : OBJECTIVE: To evaluate data of quantitative anal sphincter EMG in normal controls and to compare them with patients with multiple system atrophy (MSA). METHODS: Quantitative anal sphincter EMG were performed on 100 normal controls and 11 patients with MSA to characterise EMG data in these two groups. RESULTS: In the normal controls, there was a trend for increased motor unit potential (MUP) amplitude, duration, area, and polyphasicity with advancing age. Patients with MSA exhibited similar MUP size and fibre density. Significant differences were found only in parameters of the recruitment pattern, which were reduced in MSA, with a diminution in the number of active MUPs during rest. CONCLUSIONS: These results may reflect either decreased number of motor cells in Onuf's nucleus without significant consequential reinnervation, or upper motor neuron involvement affecting the anal sphincter in MSA. They further underline the importance of comparative data for age matched controls.